Multi-pulsed white light sintering of printed Cu nanoinks - Han, Won-Suk; Hong, Jae-Min; Kim, Hak-Sung; Song, Yong-Won (IOP PUBLISHING LTD, 2011)
Pulse management of white light to maximize the sintering efficiency of a rapid (msec) and substrate-protective method, intense pulsed light (IPL), was studied systematically with a printable Cu nanoink. An excessive pulse energy that induces deleterious defects on the Cu film along with damage on a plastic substrate was dissipated into multiple sub-pulses while maintaining a total energy budget over the threshold level for successful Cu sintering. Electrical properties of the metal layers were analyzed in conjunction with pulse formation factors such as average energy, pulse duration, peak power and pulse number to determine their respective effects on IPL sintering. In the quantitative results, the optimized sintering conditions of copper nanoparticles with a mean diameter of 30 nm and a fixed total irradiated pulse energy of 32 J cm(-2) were a pulse number and pulse width of >4 and <3 msec, respectively.
Keywords: OF-THE-ART; INK; NANOPARTICLES; ELECTRONICS; POLYMERS; FUTURE